Evolution of habitat quality and analysis of influencing factors in the Yellow River Delta Wetland from 1986 to 2020 - Zhang, Honglu; Wang, Fuqiang; Zhao, Heng; Kang, Pingping; Tang, Lei (Frontiers in Ecology and Evolution, 2022)
The assessment of habitat quality plays an important role in the effective conservation of wetland biodiversity. The increasing human activities and climate change posed a great threat to the biodiversity of the Yellow River Delta Wetland. In this study, we first analyzed the spatial and temporal evolution characteristics of habitat quality in the Yellow River Delta Wetland under the evolution of the shoreline after runoff-sediment variability (1986-2020) using the InVEST-habitat quality model and then identified the dominant influence factors on habitat quality based on Geographical Detector. Finally, we analyzed the impacts of different reclamation activities on habitat quality using the elasticity index. The results showed that the habitat quality of the Yellow River Delta Wetland decreased from 0.4798 in 1986 to 0.4078 in 2020, with high values of habitat quality concentrated in mudflat wetlands and low values of habitat quality concentrated in construction land and salt pans. The results of the geographical detector analysis showed that the influence of human activities on habitat quality was stronger than climatic factors. Human activities, mainly reclamation activities, are the main reason for the decline of habitat quality in the Yellow River Delta Wetland. The elasticity index analysis showed that the elasticity of all three types of reclamation activities, namely, culture ponds, construction land, and salt pans, were negative from 1986 to 2005, 2005 to 2020, and 1986 to 2020. The reclamation activities had a negative impact on habitat quality. The habitat quality of the Yellow River Delta Wetland was most sensitive to the change in reclamation intensity of construction land from 1986 to 2020, and the sensitivity of the change of habitat quality to the change of reclamation intensity of culture ponds and salt pans was strengthening. This study can provide a scientific basis for mitigating the tradeoff between biodiversity conservation and rapid social development in the Yellow River Delta Wetland in the future.